ETV6-ACSL6 fusion gene in myeloid neoplasms: clinical spectrum, current practice, and outcomes - Xia Wu; Hao Cai; Yu Qiu; Jian Li; Dao-bin Zhou; Xin-xin Cao (Orphanet Journal of Rare Diseases, 2020)
Abstract Background ETV6-ACSL6 is a fusion gene rarely reported in myeloid malignancies, and its clinical characteristics, proper treatment strategies, and effect on prognosis are poorly understood. Results Sixteen patients with the ETV6-ACSL6 fusion gene were identified, with a median age of 50 years. Twelve patients were male. Clinical diagnoses included chronic eosinophilic leukemia, not otherwise specified, acute myeloid leukemia, and other types of myeloproliferative and myelodysplastic disorders. Ten out of 12 patients had increased levels of eosinophils, and four out of five had increased levels of basophils in peripheral blood. Treatment with tyrosine kinase inhibitors was ineffective. The prognosis of the patients was poor, with seven patients dying within 1 year. Conclusions Patients with the ETV6-ACSL6 fusion gene mainly present with myeloproliferative and myelodysplastic disorders, typically with increased eosinophils and/or basophils and poor survival. Intensive therapies such as allogenic stem cell transplantation should be an initial consideration for eligible patients.